2013
DOI: 10.1038/sj.bdj.2013.329
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulphidemia: the significance of dimethyl sulphide in extra-oral, blood borne halitosis

Abstract: Halitosis is a symptom and not a diagnosis. Rather, the topic represents a spectrum of disorders, including intra-oral, otorhinolaryngological, metabolic, systemic, pulmonary, psychological and neurological conditions. Halitosis may be the third most common trigger for patients to seek dental care and can cause significant impact on patient quality of life. About 10% of all genuine halitosis cases are attributed to extra-oral processes. Some authorities have reported that the nasal cavity and the oropharynx ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 152 publications
1
25
0
Order By: Relevance
“…This condition is transient, disappearing following normal oral hygiene after awakening. However, pathological halitosis is more intense, persistent, and offensive, requiring treatment to eliminate its cause, and can be due to extra- or intra-oral factors [4]. Physiological halitosis can be persistent, but may not be offensive to others, while the pathological condition is offensive and can continue while its source exists [2].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is transient, disappearing following normal oral hygiene after awakening. However, pathological halitosis is more intense, persistent, and offensive, requiring treatment to eliminate its cause, and can be due to extra- or intra-oral factors [4]. Physiological halitosis can be persistent, but may not be offensive to others, while the pathological condition is offensive and can continue while its source exists [2].…”
Section: Introductionmentioning
confidence: 99%
“…The basic pathophysiological process is microbial degradation of sulfur containing amino acid substrates, for example, methionine, cysteine, and cysteine. [5] Bacterial metabolism of these kinds of amino acids leads to metabolites including many compounds, such as volatile sulfur compounds (VSC), for example, hydrogen sulfide (H 2 S), methyl mercaptan (MM, CH 3 SH), dimethyl sulfide, and skatole, indole. [6] The main odorants implicated in intraoral halitosis are MM and H 2 S. [7] …”
Section: Introductionmentioning
confidence: 99%
“…About 10% to 20% of all genuine halitosis cases are attributed to extra-oral diseases, [5] including upper and lower respiratory tract disorders, gastrointestinal disorders, some systemic diseases, metabolic diseases, medications, and cancer. [4] Some authorities have reported that the ears, nose, and throat (ENT) are the most common sites of origin of extra-oral halitosis, [5] and it is well established that various ENT disorders and symptoms may be a manifestation of gastroesophageal reflux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many people think that they have halitosis, are not serious about problem. Only significant percentage of people feels that they have halitosis 12 and when professionally examined it is not. Some have genuine halitosis but on examination it is found that the odor is caused due to bacteria present in the plaque deposited on cervical region of tooth and on the back of the tongue.…”
Section: 5005/jp-journals-10024-1757mentioning
confidence: 99%